2016
DOI: 10.1186/s12906-016-1468-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of osteopathic treatment on pulmonary function and chronic thoracic pain after coronary artery bypass graft surgery (OstinCaRe): study protocol for a randomised controlled trial

Abstract: BackgroundCoronary artery bypass graft surgery (CABG) is an effective and widespread coronary revascularisation technique, nevertheless there are a number of long-term postoperative complications from which patients can suffer. One year after CABG surgery pulmonary function is decreased by 12% and 30% of the patients suffer from chronic thoracic pain. To date and to our knowledge there are no effective treatments for these conditions. The aim of the present clinical trial is to explore the effectiveness of ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Especially in the pulmonary function, there were a few reports to treat the latter conditions. Roncada reported that osteopathic treatments might be effective treatment for decreased pulmonary function, chronic thoracic pain and diminished thoracic mobility after CABG surgery [20]. And then, inspiratory muscle training insertion in the preoperative period to cardiac surgery indicated an improvement in forced vital capacity and maximum voluntary ventilation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the pulmonary function, there were a few reports to treat the latter conditions. Roncada reported that osteopathic treatments might be effective treatment for decreased pulmonary function, chronic thoracic pain and diminished thoracic mobility after CABG surgery [20]. And then, inspiratory muscle training insertion in the preoperative period to cardiac surgery indicated an improvement in forced vital capacity and maximum voluntary ventilation [21].…”
Section: Discussionmentioning
confidence: 99%
“…A homeopátiás szereket több tanulmány vizsgálta, elsősorban ortopédiai műtétek utá ni fájdalomcsillapítás szempontjából, ám nem találták a készítményeket effektív analgetikumnak, bár a posztope ratív duzzanatot csökkenthetik [42,43]. A manuálterá piát hasznosnak találták CABGműtét utáni fájdalomcsil lapításban és a műtét utáni légúti szövődmények megelőzésében [44,45]. A masszázs alkalmazható a szorongás csökkentésében, segíti a posztoperatív fájda lomcsillapítást és alkalmazható az intenzív terápia során is [46][47][48][49].…”
Section: Az Egyes Gyógymódok Megítéléseunclassified